2004
DOI: 10.1016/s1364-8152(03)00154-3
|View full text |Cite
|
Sign up to set email alerts
|

Modular ecosystem modeling

Abstract: The modular ecosystem modeling approach was used to create a flexible landscape model structure that is easy to modify and extend for particular case studies and applications. The Library of Hydro Ecological Modules (LHEM; http://iee.umces.edu/LHEM) includes modules that describe hydrologic processes, nutrient cycling, vegetation growth, decomposition, etc., both locally and spatially. LHEM is implemented within the framework of the Spatial Modeling Environment (SME; http://iee.umces.edu/SME3) that integrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Argent 2004;Lam et al 2004;Voinov et al 2004;Poch et al 2005;Pereira et al 2006). From a technical point of view, one can opt to build a new model for each application (integrative approach) or to utilize existing models where possible (combinatory approach).…”
Section: Integrating and Combining Modelsmentioning
confidence: 99%
“…Argent 2004;Lam et al 2004;Voinov et al 2004;Poch et al 2005;Pereira et al 2006). From a technical point of view, one can opt to build a new model for each application (integrative approach) or to utilize existing models where possible (combinatory approach).…”
Section: Integrating and Combining Modelsmentioning
confidence: 99%
“…Because of the lack of sustained monitoring efforts, forecasting vegetation scenarios are difficult and prone to unacceptable levels of uncertainty (Finzi et al 2011). Although a variety of vegetation models have been developed (see review by Woodward and Lomas 2004) incorporating both correlative and mechanistic approaches (e.g., Voinov et al 2004), application of these are problematic for alpine ecosystems for a few key reasons. Because alpine communities can be climatically decoupled from those nearby (Körner 1999), parameterizing both correlative and mechanistic models may be difficult if the specific environmental variables at the plot level are not described accurately through space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Voinov et al (2004) suggested that infiltration rate of the top soil layer is equal to rainfall intensity before soil saturation is reached. In fact, some studies suggested that the rate of infiltrated water from a typical cover system is correlated to the degree of saturation of the soil, soil moisture retention characteristic, and climatic factors (e.g.…”
Section: Soil Storagementioning
confidence: 99%